The transformation of politicised religion: from zealots into leaders - Elsenhans, Hartmut; Ouaissa, Rachid; Schwecke, Sebastian; Tétreault, Mary Ann (Ashgate, 2015)
New cultural identitarian political movements in South Asia, the Middle East, and Northern Africa / Rachid Ouaissa and Sebastian Schwecke --. - Algeria's Islamists in times of political change : an exceptional case? / Rachid Ouaissa --. - The trivialization of Hindu nationalism and the reconfiguration of the Indian bourgeoisie / Sebastian Schwecke --. - Globalization and Islamic radicalism in the Arab Gulf region / Mary Ann Tétreault --. - The economic ideology of Hasan al-Banna and the Egyptian Muslim Brotherhood / Ivesa Lübben --. - The AKP or the success of a hybrid / Gérard Groc --. - Similarities and differences in the strategies and programs of the BJP and the Congress in India / Randhir B. Jain --. - Power games or programmatic evolution in the BJP / Klaus Julian Voll --. - Middle classes and new cultural-identitarian policital movements : perspectives / Hartmut Elsenhans --. - How to build a viable economic policy on Islamic foundations the case of the MSP party, Algeria / Abdelkrim Dahmen --. - The Bharatiya Janata Party : identitarianism and governance agenda / Rajvir Sharma --. - Rivalry, failure of the secular nationalists, geography, history : embedding the rising new cultural-identitarian movements in Africa and Asia in the emerging multipolar system / Hartmut Elsenhans